2015
DOI: 10.1111/faf.12134
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats

Abstract: Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be 'best practice'. To identify future knowledge-needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Brief examples and performance‐based analyses are used to develop guidance on best practices for a wide range of fisheries and associated management systems. Building on previous analyses of the impacts and management of trawling activities (Collie et al, ; Hiddink et al, , ; Pitcher et al, ; Sciberras et al, ), we address multiple knowledge gaps identified in a prioritization exercise concerned with reducing the environmental impacts of trawling (Kaiser et al, ). The resulting guidance on best practices is intended to help managers and the industry minimize environmental impacts of trawling per unit weight or value of landed fish, while achieving a sustainable level of fish production.…”
Section: Introductionmentioning
confidence: 99%
“…Brief examples and performance‐based analyses are used to develop guidance on best practices for a wide range of fisheries and associated management systems. Building on previous analyses of the impacts and management of trawling activities (Collie et al, ; Hiddink et al, , ; Pitcher et al, ; Sciberras et al, ), we address multiple knowledge gaps identified in a prioritization exercise concerned with reducing the environmental impacts of trawling (Kaiser et al, ). The resulting guidance on best practices is intended to help managers and the industry minimize environmental impacts of trawling per unit weight or value of landed fish, while achieving a sustainable level of fish production.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, bottom trawls are relatively unselective fishing gears (Cashion et al , ), for this reason the wider cost‐benefit of deep‐water fisheries should be considered when reviewing fisheries regulations (Mangi et al , ). Collecting further data on the biodiversity and ecosystem functioning of deep‐sea communities is important to consolidate knowledge and assess state and trends and to provide scientific‐based information towards conservation and sustainable exploitation of marine resources (Ehler & Douvere, ; Kaiser et al , ).…”
Section: Scope For Future Workmentioning
confidence: 99%
“…In truth, there is a trade-off to be balanced. Identifying knowledge needs and transitioning toward "best practices" has been suggested as a pathway toward balancing the trade-off between the effects of mobile fishing on the seabed and the benefits of fish production for food security (Kaiser et al 2015). In that study, the authors developed and prioritized 108 knowledge gaps associated with bottom trawling.…”
Section: Introductionmentioning
confidence: 99%
“…In the top ten was the need to determine "what gear configurations exist to mitigate habitat impacts and how can these benefits be quantified?" (Kaiser et al 2015). Indeed, the development of gear modifications to reduce the seabed impact of bottom trawls is not a new field of investigation.…”
Section: Introductionmentioning
confidence: 99%